The Impact of Regulatory and Supervisory Structures on Bank Risk and Returns : Evidence from Dual Banking System - Raj, Mark Sanjay (2013)
This project is a discussion in regard to dual banking systems and how banking regulatory and supervisory frameworks affect bank efficiency. The dual banking system in question here is one where both commercial conventional banks co-exist with Islamic or Sharia compliant financial services. This project examines 11 countries who are OIC members and have adopted either wholly or partially the requirements of Basel II and uses data from Bankscope 2.0 from the 5 year period ending 2010. It examines to what extent similar regulations would affect the 2 banking systems and how best could policymakers enact frameworks which would then help promote the efficiency of banking where both sectors are present.